2017
DOI: 10.1111/ijet.12123
|View full text |Cite
|
Sign up to set email alerts
|

Virtual trade between separated time zones and growth

Abstract: The purpose of this paper is to propose a model where trade has a direct and positive impact on growth rate of two trading nations beyond the level effect. We use the idea of virtual trade in intermediates induced by non‐overlapping time zones and show how trade can increase the equilibrium optimal rate of growth. In this structure the trade impact goes beyond the level effect and directly causes growth. Typically standard models of trade cannot generate an automatic growth impact. Virtual trade may allow prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…They showed that a reduction of the transaction cost of trade in services due to the advancement of the communications networks increases the endogenous growth rates of both countries. Marjit and Mandal (2017) extended the Kikuchi-Marjit model to an AK-type optimal endogenous growth model. They showed that the liberalization of trade in services can raise not only the level of the GDP of the country but also the growth rate.…”
Section: Related Literaturementioning
confidence: 99%
“…They showed that a reduction of the transaction cost of trade in services due to the advancement of the communications networks increases the endogenous growth rates of both countries. Marjit and Mandal (2017) extended the Kikuchi-Marjit model to an AK-type optimal endogenous growth model. They showed that the liberalization of trade in services can raise not only the level of the GDP of the country but also the growth rate.…”
Section: Related Literaturementioning
confidence: 99%
“…2. For example, India’s service sector has grown rapidly after liberalization and this is particularly because of software exports which require a virtual platform. Marjit and Mandal (2017) points out that this growth in service exports, to a great extent, is the result of India’s geographic location.…”
Section: Notesmentioning
confidence: 99%
“…To exploit this possibility, TZ of trading partners or countries must be non-overlapping [3]. This issue has been explained very nicely in Marjit (2007), Kikuchi (2011), Kikuchi and Marjit (2011), Kikuchi et al (2013), Anderson (2014), Dettmer (2014), Head et al (2009), Matsuoka and Fukushima (2010), Nakanishi and Long (2015), Mandal et al (2018b), Fink et al (2005), Mandal (2015), Marjit and Mandal (2017), etc. [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations